Variation of the photosynthetic activity and pigment composition in two morphotypes of Durvillaea antarctica (Phaeophyceae) in the sub-Antarctic ecoregion of Magallanes, Chile - Mendez, F.; Marambio Gallardo, Johanna Valeska; Ojeda Villarroel, Jaime Andrés; Rosenfeld, S.; Rodriguez, J. P.; Tala, F.; Mansilla Muñoz, Andres Omar (My University, 2019)
The environment of the sub-Antarctic ecoregion of Magallanes is highly heterogenous due to the influence of three oceans (Pacific, Atlantic, and Southern) and the effects of postglacial events such as the Last Glacial Maximum. In the sub-Antarctic ecoregion of Magallanes, the presence of two morphotypes of Durvillaea antarctica has recently been recorded that are related to the specific hydrodynamic configuration of the sites in the region. This study investigates the photosynthetic activity and pigment composition during two periods of the year in these two morphotypes of D. antarctica. One of them has broad and laminar fronds and occurs in wave-protected environments, while the other morphotype is characterized by cylindrical and elongated fronds and inhabits wave-exposed environments. The adult specimens of the elongated-cylindrical morphotype were collected in Seno Otway (53.1 degrees S, 71.5 degrees W) and the specimens of the "laminar" morphotype in Bahia el Aguila, San Isidro (53.7 degrees S, 70.9 degrees W). ETRmax, alpha, and E-k as parameters of the ETR-E curves were higher for the laminar than the elongated-cylindrical morphotype, resulting in significant values. The concentration of fucoxanthin was statistically higher for the morphotype laminar compared to the morphotype elongated-cylindrical. Both morphotypes exhibited different photosynthetic activities, perhaps attributed to their morphology, floatation capacity, and environment.
Keywords: durvillaea antarctica; phaeophyceae; morphology; photosynthesis; pigments; sub-antarctic; ecophysiology